Investigation of antropometric and performance responses of core exercises in volleyball players - Boz, H. K. (International Journal of Applied Exercise Physiology, 2020)
The aim of the study is to investigate the effect of core exercise on performance in volleyball players. In the study, the effect of core exercises performed as statically and dynamically on body composition, agility related to anaerobic strength tests and core stabilization tests in volleyball players was investigated. Thirty volleyball players participated in the study, 10 of them did volleyball exercises, the other group of 10 did volleyball and core exercises together for 2 days in a week about 30 minutes during 9 weeks. However, the remaining 10 subjects did not perform any activities as a control group. In the analysis of obtained values SPSS 25 program was used. Significant differences were found at the level of p < 0.05 in all comparisons in-group, pre,and post-tests of anthropometric measurements, body weight and body mass index. It was found that there were significant differences at the level of p < 0.05 in deadlift and doing sit-ups tests in the comparisons between the first and last measurements ofall anthropometric measurements and in all measurements except in the control groups of the plank, shuttle and isometric tests. In all core tests, the measurements of the volleyball core group are statistically higher than the other two groups. In the first and last test comparisons within the group, there was a significant difference at p < 0.05 level in long jump, agility 550 and arrowhead agility tests. However, in all dynamic field tests, volleyball core increased the test time more than the volleyballand control group. On the other hand, an increase in the long jump test period of the control group is observed. While the test*group interaction is observed in the Arrowhead feature, this interaction results from the intra-group development of the volleyball core and volleyball test groups. As a result, based on the findings obtained, core exercise practices were found to improve core strength. Based on this development, it can be thought that core exercise programs will have a positive effect on the performance of volleyball athletes.